2020
DOI: 10.1186/s12939-020-1128-6
|View full text |Cite
|
Sign up to set email alerts
|

All-cause mortality rate in China: do residents in economically developed regions have better health?

Abstract: Background: Urban-rural disparities have been extensively investigated, while most investigators overlooked urbansuburban-rural variations in population health. Although regional disparities in East-West China have been largely discussed, limited attention has been directed to the interaction between regional differences and urban-suburbanrural disparities. This study aims to analyze urban-suburban-rural variations in all-cause mortality rates across four geographic regions in China. Methods: Data came from Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Fourth, previous studies have demonstrated the influence of contextual factors on access to healthcare and mortality-such as the level of neighborhood socioeconomic status and development, availability of healthcare facilities in a community, number of medical professionals within the facilities, etc. [51,52]. However, due to the lack of data on such measures in the CLHLS, we were unable to directly model the effects of these potential contextual factors.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, previous studies have demonstrated the influence of contextual factors on access to healthcare and mortality-such as the level of neighborhood socioeconomic status and development, availability of healthcare facilities in a community, number of medical professionals within the facilities, etc. [51,52]. However, due to the lack of data on such measures in the CLHLS, we were unable to directly model the effects of these potential contextual factors.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies provided insufficient evidence on the interaction between the geographic gradient and urban-rural settings, even though the cross-sectional study based on a National Epidemiological Survey of Stroke in China (NESS-China) indicated a general north-to-south geographical gradient in stroke prevalence in conjunction with the heavy disease burdens in rural areas [ 7 ]. As urbanization has been accelerated over the past few decades, the regional differences among urban areas may have diminished over time [ 12 ]. Therefore, more attention should be directed to geographic disparities in rural areas when considering the priority of public health intervention.…”
Section: Discussionmentioning
confidence: 99%
“…7 As urbanization has been accelerated over the past few decades, the regional differences among urban areas may have diminished over time. 12 Therefore, more attention should be directed to geographic disparities in rural areas when considering the priority of public health intervention.…”
Section: Comparison With Existing Researchmentioning
confidence: 99%
See 2 more Smart Citations